Obyčejná nemoc - apendicitida - Lukáš, Karel (Vnitrni lekarstvi, 2015)
Appendicitis is the most common abdominal emergency. While the clinical diagnosis may be easy in patients who present with classic signs and symptoms. Atypical presentations may result in diagnostic embarrassment and delay in treatment. Typical sign is abdominal pain. Furthermore, it can be nausea, vomiting and anorexia. Abdominal examination reveals localised tenderness and muscular rigidity in the right lower abdominal quadrant. Laboratory data usually reveal an elevated leukocytosis with a left shift and elevated C-reactive protein. To establish the diagnosis greatly help native abdominal X-ray, ultrasound or CT. In 1889, an appendectomy was accepted as the standard treatment, because they save lives and since then dictum: removal of the inflamed appendix changed, it is necessary!
Keywords: apendicitida; bolesti břicha; Abdominal Pain; lidé; C-Reactive Protein; C-reaktivní protein; apendektomie; Appendicitis; Appendectomy; Humans